The construction of medical records as the expression of health professionals' practice - Mesquita, Ana Maria Otoni; Deslandes, Suely Ferreira (Saúde e Sociedade, 2010)
The focus of the paper is the construction of medical records by health professionals in two public health assistance services for pregnant teenagers. The medical record, beyond its judicial character, must be understood nowadays as a tool for promoting communication between the staff members, as well as between staff and patients, an instrument that mediates communication actions. Based on Michel Foucault's historical approach to registration as part of a disciplinary technology that emerges together with the modern hospital and clinical view, it was identified that health professionals neglect the communicative aspect, according to the concept of 'communicative acting' developed by Jürgen Habermas, of the registration action, and show a conception of clinical procedures based on 'secrecy' rather than a social construction of new knowledge.